2017
DOI: 10.1016/j.icarus.2016.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Simulated space weathering of Fe- and Mg-rich aqueously altered minerals using pulsed laser irradiation

Abstract: Simulated space weathering experiments on volatile-rich carbonaceous chondrites (CCs) have resulted in contrasting spectral behaviors (e.g. reddening vs bluing). The aim of this work is to investigate the origin of these contrasting trends by simulating space weathering on a subset of minerals found in these meteorites. We use pulsed laser irradiation to simulate micrometeorite impacts on aqueously altered minerals and observe their spectral and physical evolution as a function of irradiation time. Irradiation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 64 publications
1
20
0
Order By: Relevance
“…Finally, our results also suggest that weathering of FeS, and possibly other sulfides, via micrometeorite impacts is not responsible for the decrease in spectral slope (bluing) that was observed in previous studies (Gillis-Davis et al, 2017). Thus, other minerals, such as carbonaceous material, may be more important for driving the observed spectral decrease, as well as the two-step spectral trend noted recently (Kaluna et al, 2017). Future studies will focus on studying space weathering effects in these other minor components present in the asteroid regolith.…”
Section: Implication For Space Weathering On Airless Bodies Via Microsupporting
confidence: 79%
“…Finally, our results also suggest that weathering of FeS, and possibly other sulfides, via micrometeorite impacts is not responsible for the decrease in spectral slope (bluing) that was observed in previous studies (Gillis-Davis et al, 2017). Thus, other minerals, such as carbonaceous material, may be more important for driving the observed spectral decrease, as well as the two-step spectral trend noted recently (Kaluna et al, 2017). Future studies will focus on studying space weathering effects in these other minor components present in the asteroid regolith.…”
Section: Implication For Space Weathering On Airless Bodies Via Microsupporting
confidence: 79%
“…The laser was incident at 60°measured with respect to the sample normal, operated at 20 Hz with a 10 ns pulse length, and the power density was varied from about 10 to 250 μJ/cm 2 /pulse. This power is about 10 6 times less intense than what is typically used for laser simulations of micrometeorite impacts (Kaluna et al, 2017;Loeffler et al, 2008;Matsuoka et al, 2015). The experiments were carried out at room temperature (25°C) which, although cooler than typical dayside surface temperatures, is within expected temperature ranges on Mercury.…”
Section: Methodsmentioning
confidence: 99%
“…In the laboratory, several experiments have been performed on carbonaceous chondrites and analog materials to simulate the effects of micrometeoroid bombardment (via laser irradiation) and solar wind exposure (via ion irradiation). A common result of these simulations is the production of opaque materials (Gillis‐Davis et al, ; Gillis‐Davis et al, ; Matsuoka et al, ; Lantz et al, ; Thompson et al, ), notably carbonized materials (Kaluna et al, ; Moroz et al, ); these experiments and results are summarized briefly in the section S5. In particular, Lantz et al () demonstrated that the initial composition of a material plays an important role in determining whether it becomes bluer or reddens upon weathering.…”
Section: Links With Space Weatheringmentioning
confidence: 99%